The development of a financial toxicity patient‐reported outcome in cancer: The COST measure. Issue 20 (20th June 2014) - de Souza, Jonas A.; Yap, Bonnie J.; Hlubocky, Fay J.; Wroblewski, Kristen; Ratain, Mark J.; Cella, David; Daugherty, Christopher K.
Abstract : BACKGROUND: Considering patients' experience is essential for optimal decision‐making. However, despite increasing recognition of the impact of costs on oncology care, there is no patient‐reported outcome measure (PROM) that specifically describes the financial distress experienced by patients. METHODS: The content for a comprehensive score for financial toxicity (COST) was developed with a stepwise approach: step 1) a literature review and semistructured, qualitative interviews with patients for content generation; step 2) patients' assessment of the items for importance to their quality of life; step 3) pilot testing assessing interitem (IIC) and item–total (ITC) correlations to identify redundancy (Spearman rho, >0.7) and statistically unrelated content ( P > .05); and step 4) exploratory factor analysis. Sociodemographic data were collected. RESULTS: In total, 155 patients with advanced cancer who were receiving treatment (20 patients in step 1, 35 patients in step 2, and 100 patients in steps 3 and 4) participated in the PROM development. In step 1, the literature was reviewed, and 20 patients generated 147 items, which were reduced to 58 items because of redundancy. In step 2, 35 patients rated the 58 items on importance, and 30 items were retained. In step 3, 46 patients assessed the 30 items, 14 items were excluded because of high IIC, and 3 were excluded because of nonsignificant ITC. In step 4, 2 items were discarded because of poor loadings in a factor analysis of 100 patients, resulting in an 11‐item PROM. CONCLUSIONS: The content for a financial toxicity PROM was developed in 155 patients. The provisional COST measure demonstrated face and content validity as well as internal consistency and should be validated in larger samples. Cancer 2014;120:3245–3253. © 2014 American Cancer Society . Abstract : There is no patient‐reported outcome measure that specifically describes the financial distress experienced by cancer patients. The authors describe the development of a novel, 11‐item financial measure in 155 patients with advanced cancer.